7.6% CZGSe Solar Cells Thanks to Optimized CdS Chemical Bath Deposition. Issue 13 (8th May 2018) - Choubrac, Leo; Brammertz, Guy; Barreau, Nicolas; Arzel, Ludovic; Harel, Sylvie; Meuris, Marc; Vermang, Bart
Abstract : In this study, CdS chemical bath deposition is investigated to improve the performance of thin film solar cell based on Cu2 ZnGeSe4 /CdS heterojunction. The influence of both the bath temperature and the dipping duration on the CdS thin film properties are explored thanks to the combination of scanning electron microscopy (SEM) and Raman spectroscopy, while the photovoltaic parameters of the resulting solar cells are discussed from current–voltage ( I–V ) and external quantum efficiency (EQE) measurements. The highest efficiency achieved herein (without antireflection coating) is 7.6%. Although it represents 35% relative improvement compared to previous best efficiency, this champion device is still limited by interface recombination. Different strategies are finally proposed to further increase the performance of these solar cells. Abstract : While several authors report partial substitution of germanium for copper to improve kesterite Cu‐Zn‐Sn‐(S, Se) solar cells, the complete substitution lowers devices efficiency, partly because of absorber/buffer recombination. Hence, here CdS buffer layer growth mechanism are studied by Raman and SEM in order to improve the Cu‐Zn‐Ge‐Se/CdS heterojonction. It results in a 7.6% efficient device, the highest reported for Sn‐free kesterite solar cell.